2013
DOI: 10.1063/1.4773830
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-terminated detonation nanodiamond: Impedance spectroscopy and thermal stability studies

Abstract: In this paper, we investigated the effect of hydrogen termination on the electrical properties and impedance spectra of detonation nanodiamond. The impedance spectra revealed that the hydrogen-termination process increases the electrical conductivity by four orders of magnitude at room temperature. An equivalent circuit has been proposed to correlate with the conduction mechanism. Arrhenius plot showed that there were two different activation energy levels located at 0.089 eV and 0.63 eV between 50 º C and 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Recently, Su et al reported that hydrogenation of detonation ND by hydrogen plasma treatment increased the electrical conductivity, as estimated by impedance spectroscopy, by four orders of magnitude. 23 In the present study, we investigated the surface hydrogenation of NDs by high temperature treatment in hydrogen gas and the resistivity of the NDs as a function of treatment temperature. Based upon the estimation of the surface oxygen content and the sp 2 /sp 3 carbon ratio of the treated NDs, the decrease in the resistivity was found to be consistent with the transfer doping caused by the surface hydrogenation of ND.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Su et al reported that hydrogenation of detonation ND by hydrogen plasma treatment increased the electrical conductivity, as estimated by impedance spectroscopy, by four orders of magnitude. 23 In the present study, we investigated the surface hydrogenation of NDs by high temperature treatment in hydrogen gas and the resistivity of the NDs as a function of treatment temperature. Based upon the estimation of the surface oxygen content and the sp 2 /sp 3 carbon ratio of the treated NDs, the decrease in the resistivity was found to be consistent with the transfer doping caused by the surface hydrogenation of ND.…”
Section: Introductionmentioning
confidence: 99%
“…Loh et al reported the efficient reduction of oxidized DNDs by exposing the nanoparticles to hydrogen plasma [56]. Hydrogen-terminated NDs are hydrophobic, stable in suspension, and display p -type conductivity which can facilitate further surface modifications [57, 58]. …”
Section: Synthesis and Functionalization Of Ndsmentioning
confidence: 99%
“…The IS technique has been effectively utilized to analyse the electric transport of bulk diamond and nanodiamonds, previously. [16][17][18][19] However, no efforts have been made on the more complex diamond MOS structure.…”
Section: International Center For Materials Nanoarchitectonics (Mana)mentioning
confidence: 99%